Study on the Wear Modes of PVD Films Using Different Concentrations of Al2O3 Abrasive Particles and Textured Rotating Balls - Pinto, Gustavo Filipe (2023)
Abrasive wear is a wear mechanism that results in a loss of material from the interaction of a surface with hard particles. This type of wear is frequently found in the surface of machining tools. Microscale abrasion equipment is often used to characterize the resistance to abrasive wear of a surface. The different parameters able to control micro-abrasion wear tests, such as ball rotation, sliding distance between ball and surface sample, abrasive slurry concentration, normal load acting on the sample, and abrasive flow rate over the sample, have been widely studied. The combination of different variables, including sliding distance, concentration of abrasive particles, their hardness, and size of abrasive particles, promotes the transition between two-body, three-body, or mixed abrasive wear modes. However, the influence of the ball surface on the dragging of abrasive particles, which is reflected in the wear modes, is still poorly studied. One of the variables possible to control and less studied is the influence of the ball surface texture on the dragging of abrasive particles in microabrasion wear tests. This work intends to correlate the effect of different testing times (500, 1000, and 1500 cycles) and different concentrations of 3 m Al2O3 abrasive slurry (25, 35, and 45 g/100 mL) on the micro abrasion resistance of a TiN thin coating film, using balls of AISI 52100 steel whose texture and roughness were prepared by 60 s chemical etching. The rotation speed of each test was 80 rpm, applying a normal load of 2 N. Subsequently, the craters were carefully analyzed using SEM to evaluate the transition of the wear mode as a function of the applied load, the abrasive particle concentration, and the sliding distance. The textured ball tracks were observed via SEM to assess the particle dynamics. The results showed that, contrarily to what is reported in the literature regarding wear modes where rolling is promoted with increasing abrasive concentration, in this work grooving took place instead. This is a result of the rough balls use in the experiments which, due to the embedment of abrasive particles in the ball grooves, promotes the abrasion mechanism. The higher the abrasive concentration, the higher the grooving mechanism, since more particles are available to scratch the surface.